PHARMACOLOGICAL AND SURGICAL TREATMENT OF OBESITY: INTEGRATING THE ROLES OF INFLAMMATION AND GUT DYSBIOSIS- REVIEW - Karolina Zarówna; Weronika Pura; Jakub Mazur; Jakub Marciniak; Mateusz Kosowski; Dominika Matecka; Wiktor Śliwiński; Daniel Chołuj (International Journal of Innovative Technologies in Social Science, 2026)
Obesity is a metabolic disease characterized by chronic systemic inflammation and dysbiosis of gut microbiota. This review explores relationships between obesity, inflammatory pathways, and gut microbiome composition within a clinical perspective, concentrating on pharmacological and surgical options. Current therapeutic strategies consist of GLP-1 receptor agonists, orlistat, naltrexone-bupropion combination therapy, and bariatric surgery. Significantly, therapeutic advantages go far beyond weight decrease to consist of improved microbial diversity, decreased inflammation (reflected as a decrease in inflammatory markers such as CRP, IL-6, and TNF-α), and metabolic outcomes. The present review demonstrates that successful obesity therapy requires both the normalisation of gut microbial function and the elimination of systemic inflammation, underscoring the significance of microbiota-related modalities for total obesity treatment.